ANALISIS HARGA POKOK PRODUKSI TELUR AYAM DENGAN MENGGUNAKAN METODE FULL COSTING DI PETERNAKAN CV.SADAK KECAMATAN SUMBAWA - Dewi Febriyanti; Yadi Hartono; Syahdi Mastar; Muhammad Aries Zukhri Angkasa; Lukman Hakim (JURNAL SOSIAL EKONOMI PERTANIAN, 2026)
This study aims to determine the cost of production of chicken eggs using the full costing method at CV. Sadak's farm in Sumbawa District. The research method used is descriptive quantitative with a full costing approach, where all production cost components, including raw material costs, labor costs, and factory overhead costs, are calculated comprehensively. Data for this study were obtained through observation, interviews, documentation, and recording of production costs during the study period. The results indicate that total production costs during the period reached Rp 883,448,750, with raw material costs accounting for 85.74%, labor costs 9.16%, and factory overhead costs 5.1%. Feed costs were the largest component in the production cost structure, while electricity and water costs were the smallest. The cost of production per egg was Rp 1,514.83, with an average production of 1,080 eggs per day or 32,400 eggs per month. Monthly income reached Rp 57,240,000 with a profit of Rp 8,159,513.89. The R/C ratio of 1.17 and profitability of 16.62% indicate that CV. Sadak's laying hen farming business is feasible, efficient, and profitable